HPTLC method for simultaneous determination of ascorbic acid and gallic acid biomarker from freeze dry pomegranate juice and herbal formulation - Prawez Alam; Y.T. Kamal; Saleh Ibrahim Alqasoumi; Ahmed Ibrahim Foudah; Mohammed Hamed Alqarni; Hasan Soliman Yusufoglu (Elsevier, 2019)
A new rapid, simple, sensitive and high performance thin layer chromatography (HPTLC) has been established for the simultaneous determination of ascorbic acid and gallic acid in the freeze-dried pomegranate fruit juice and herbal formulation. HPTLC method was carried out using ethyl acetate: acetone: water: formic acid, 10:6:2:2 (%, v/v/v/v)) on 20 × 10 cm glass coated silica gel 60 F254 plates and scanned at 254 nm for ascorbic acid and gallic acid. Ascorbic acid and gallic acid in the freeze-dried pomegranate fruit juice were identified by comparing their single spot at Rf = 0.54 ± 0.02 and Rf = 0.83 ± 0.01 respectively. The value of regression equation (r2 ≥ 0.9992) revealed a good linear relationship between peak area and amount of ascorbic acid and gallic acid in the range of 100-800 ng/band. The method was validated for precision, accuracy, robustness LOD and LOQ. The method proposed can be useful for routine determination of ascorbic acid and gallic acid in various crude as well as herbal formulations as a quality control tool. Keywords: Ascorbic acid, Gallic acid, HPTLC densitometry, ICH guidelines, Qualitative, Quantitative